GOOD GOVERNANCE IN THE LEADERSHIP OF THE PRINCIPAL OF SDN 2 GUNUNG MALANG IN IMPROVING THE SCHOOL BRAND IMAGE - Firmansyah, Muhammad; Yaqin, Muhammad Ainul (Erudio Journal of Educational Innovation, 2024)
This research explores the application of the concept of Good governance in the leadership of the Principal of SDN 2 Gunung Malang as an effort to improve the school's brand image. Usinga qualitative approach with a case study type, this research focuses on how the application ofgood governance principles, such as transparency, accountability and participation, canstrengthen the leadership of school principals in creating a conducive educational environmentand improving the school's reputation. The case study was carried out in depth, highlightingaspects of human resource management, infrastructure, student achievement and the quality ofgraduates at SDN 2 Gunung Malang. The results of this research provide insight into theinfluence of the implementation of good governance on school image and how appropriatepolicies can support the continued development of schools effectively and sustainably.